Cl II Malocclusion Treatment, Using the Modified Twin Block Appliance Coordinated with Fixed Orthodontics in a Postmenarche Patient - Amin Aminian; Shahriar Sarvareh Azimzadeh; Elina Rahmanian (Case Reports in Dentistry)
Functional appliances have been used for treatment of Class II patients for a long time. The main objective of therapy with functional appliances is to induce supplementary lengthening of the mandible by stimulating increased growth at the condylar cartilage. The Twin Block appliance is one of the most commonly used functional appliances. The aim of this paper is to present a case report of mandibular deficiency treatment with Twin Block appliance in a female patient whose sexual maturation (one and a half years after menarche) and cervical vertebral maturation stage indicated the end of the growth peak. The treatment started with bonding 0.022 in MBT prescription brackets on the upper arch in order to align upper teeth and create a symmetric overjet. When reaching alignment, a modified Twin Block was given to the patient for 8 months. Final coordination was achieved with fixed appliances in both arches. At the end of the treatment, profile of the patient improved, crowding was relieved, and Cl I relationship with normal overjet and overbite was achieved.